Arch of Septimius Severus in the city of Leptis Magna: قوس سبتيميوس (Elmergib Journal of Human Sciences, 2026)
This research examines the Arch of Septimius Severus in Leptis Magna, one of the most important Roman archaeological sites in Libya and North Africa. The arch was erected in honor of Emperor Septimius Severus, who was born in Leptis Magna, to celebrate his military victories and consolidate his political position within the Roman Empire during the third century AD.The research explores the arch's geographical location and its role in the city's urban planning. Situated at the intersection of major roads, it was a pivotal element in social and commercial life. The research also examines the architectural style and artistic decorations that characterize the arch, reflecting the skill of Roman art and its influence by various cultural elements.Furthermore, the research addresses the historical and archaeological significance of the arch, its role in highlighting Leptis Magna's prominence within the Roman Empire, and the stages of its discovery and restoration. In conclusion, the research confirms that the Arch of Septimius Severus is a significant cultural landmark reflecting the grandeur of Roman architecture and the historical legacy of Leptis Magna.
Keywords: Arch; Septimius Severus; Sculptures; Restoration; Leptis Magna